The peaceful home - Westgate, Alice (Marshall, 1998)
Your home should be a refuge, individual to you and expressing your tastes and dreams. An harmonious environment depends upon balancing priorities with technical know-how and imagination. First published in 1998, this inspirational and practical guide will enable you to create your own tranquil space within your home.